MOVING BEYOND FACTIONS: USING SOCIAL NETWORK ANALYSIS TO UNCOVER PATRONAGE NETWORKS AMONG CHINESE ELITES - Keller, Franziska Barbara (Journal of East Asian studies, 2016)
Informal connections play an important role in regimes all across the world, but among China's political elite, it is particularly factional affiliation that is said to structure contention over who will rule and who will fall victim to a purge. This article identifies two approaches to measuring factional ties in the literature: the exploratory approach traces alliance ties through qualitative assessment of insider sources, while the structured approach uses publicly available data to infer factions from shared characteristics. The article combines the two by arguing that informal politics is better conceptualized as a process of alliance formation shaped by an underlying social (network) structure. Among the structured approaches, coworker networks best capture the latter, but this can be further refined by noting the number of instances of working together, or by taking into account promotions that have occurred while the two individuals were coworkers.